Fine-scale movement patterns and habitat selection of little owls (Athene noctua) from two declining populations - Mayer, Martin; Šálek, Martin; Fox, Anthony David; Juhl Lindhøj, Frej; Jacobsen, Lars Bo; Sunde, Peter (PloS one, 2021)
Advances in bio-logging technology for wildlife monitoring have expanded our ability to study space use and behavior of many animal species at increasingly detailed scales. However, such data can be challenging to analyze due to autocorrelation of GPS positions. As a case study, we investigated spatiotemporal movements and habitat selection in the little owl (Athene noctua), a bird species that is declining in central Europe and verges on extinction in Denmark. We equipped 6 Danish food-supplemented little owls and 6 non-supplemented owls in the Czech Republic with high-resolution GPS loggers that recorded one position per minute. Nightly space use, measured as 95% kernel density estimates, of Danish male owls were on average 62 ha (± 64 SD, larger than any found in previous studies) compared to 2 ha (± 1) in females, and to 3 ± 1 ha (males) versus 3 ± 5 ha (females) in the Czech Republic. Foraging Danish male owls moved on average 4-fold further from their nest and at almost double the distance per hour than Czech males. To create availability data for the habitat selection analysis, we accounted for high spatiotemporal autocorrelation of the GPS data by simulating correlated random walks with the same autocorrelation structure as the actual little owl movement trajectories. We found that habitat selection was similar between Danish and Czech owls, with individuals selecting for short vegetation and areas with high structural diversity. Our limited sample size did not allow us to infer patterns on a population level, but nevertheless demonstrates how high-resolution GPS data can help to identify critical habitat requirements to better formulate conservation actions on a local scale.
Keywords: Biological Monitoring; Behavior, Animal; Strigiformes; biologický monitoring; ekosystém; pohyb; Stringiformes; Česká republika; migrace zvířat; mužské pohlaví; Czech Republic; ženské pohlaví; zvířata; Movement; chování zvířat; Female; Ecosystem; Animal Migration; Male; Animals